What Can Rubber Farmers and Institutions Do for Supply Chain Networks: The Political Economy Analysis - Saadah, Maratun; Agustiyara, Agustiyara (Pusjar SKPP Lembaga Administrasi Negara, 2022)
This research analysed the process of the supply chain of natural rubber between Tauke (collectors) and farmers and between farmers who have their rubber plantation and their tapper labour, with the institutional political economy analysis in Batanghari Regency, Jambi province. The research was descriptive research with a qualitative approach. This research used in-depth interviews with particular informants with purposive sampling and participative observation methods in certain activities. Data that had been obtained was analysed and qualitatively described. This research found that the collectors still overpowered the supply-chain process of natural rubber in the Batanghari Regency – trader, both at the village, sub-regency, and Regency levels. Other institutions, such as the auction market and crumb rubber factory, were located only in particular locations, so they were not accessible to the whole farmers in the Regency. As a result, several channels of marketing systems made different prices from what the farmers got. Institutional marketing indeed could be implemented. It has been proven by institutions such as auctions, joint venture groups, and other groups. Besides, some non–economic aspects can affect the way price parameter changes in the supply chain process, and they are; institution characteristics, marketing channel, and patronage relationship between farmers and traders. Batanghari Regency government should re-examine their plantation regulation about the marketing mechanism until the lowest level, villages. The government should have encouraged a mutual understanding among farmers so that similar efforts could occur elsewhere.